Progress report from the AMAP Board to the SAO meeting in Oulu, May 15-16, 2002. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Program (AMAP), 2002)
"1. Follow-up since Barrow Ministerial Meeting - review of the current mandate and tasks given in the Barrow Ministerial (text from the declaration is shown as italics) Endorse and adopt the Arctic Climate Impact Assessment (ACIA), a joint project of the Arctic Monitoring and Assessment Programme (AMAP) and the Conservation of the Arctic Flora and Fauna (CAFF) Working Group, in cooperation with the International Arctic Science Committee, approve the goals and objectives contained in the ACIA Implementation Plan and request that the AMAP and CAFF Working Groups, in consultation with the Sustainable Development Working Group, promote the availability of the necessary social and economic expertise to complete the assessment;" /./